Experimental Evaluation of Heat of Hydration in Concrete Incorporating Supplementary Cementitious Materials - Lada, Adveni Hesty Altisari; Sutrisno, Wahyuniarsih; Piscesa, Bambang (Journal of Civil Engineering, 2024)
This research aims to study the impact of supplementary cementitious materials on the heat of hydration of concrete. The experimental tests were performed for concrete with three size variations and seven variations of supplementary cementitious materials (SCMs) to investigate its impact on the heat of hydration. The SCMs used in this research mainly come from industrial waste materials. Fly ash (FA), ground bottom ash (GBA), and silica fume (SF) were the waste materials used in this research. Tests were carried out for seven days for each variation to observe the effect of volume changes and the addition of SCMs on the change in concrete temperature. The experimental results indicated a direct correlation between concrete volume and maximum temperature, with notable variations in temperature distribution across the concrete mass. Typically, the highest temperature was observed at the core of the concrete. Fly ash (FA) and bottom ash (BA) demonstrated an inverse relationship between their content as supplementary cementitious materials (SCMs) and the maximum temperature achieved. Increasing the proportion of FA and BA in the concrete mixture resulted in a reduction of the hydration temperature. Additionally, silica fume (SF) was found to accelerate the hydration rate, though its efficacy in lowering the heat of hydration was significant only when its content exceeded 5%.